2013
DOI: 10.1108/jfep-02-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Bank structure and failure during the financial crisis

Abstract: Purpose -This paper aims to examine the impact of charter type (national vs state), holding company structure, and measures of bank fragility on the likelihood of bank failure during the late 2000s financial crisis. Design/methodology/approach -The study estimates a series of logit regressions in an effort to identify the causes of failure and assess the role of the bank-level characteristics while controlling for the economic and regulatory environment. Findings -The empirical results indicate that establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 19 publications
4
27
0
2
Order By: Relevance
“…DeYoung et al (2009) did a comprehensive study of M&A of over 150 cases and concluded the primary causation of consolidation stemmed from innovation in financial and technical fields that created new optimal functions of operations. Lu and Whidbee (2013) show that banks that are more financially fragile are more likely to fail, as well as de novo banks. Since the 2007 financial crisis, many different factors have been deemed significant in influencing bank failures such as brokered deposits (Rossi 2010), real-estate loans (Cole and White 2011), and audit quality (Jin, Kanagaretnam, and Lobo 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…DeYoung et al (2009) did a comprehensive study of M&A of over 150 cases and concluded the primary causation of consolidation stemmed from innovation in financial and technical fields that created new optimal functions of operations. Lu and Whidbee (2013) show that banks that are more financially fragile are more likely to fail, as well as de novo banks. Since the 2007 financial crisis, many different factors have been deemed significant in influencing bank failures such as brokered deposits (Rossi 2010), real-estate loans (Cole and White 2011), and audit quality (Jin, Kanagaretnam, and Lobo 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Referring to Stiroh and Metli (2003), Lu and Whidbee (2013) and Ghosh (2015), we use the usual measure of non-performing loans as the sum of non-accrual loans and loans past due 90 days or more. Stiroh and Metli (2003) define non-accrual loans as loans not earning the predetermined interest rate either because the whole collection of principal is uncertain or since the payment of interests has not been completed.…”
Section: The Dependent Variablementioning
confidence: 99%
“…Esto mejoraría los márgenes de crédito a largo plazo ya que el crecimiento de los préstamos normalmente se recupera gracias a una economía mejorada. Existe evidencia de que una alta reserva de NPL es un predictor significativo de quiebra bancaria, y distorsiona la estructura de costos y la eficiencia del banco (Lu y Whidbee, 2013, Cucinelli, 2015. Un ejemplo de tales distorsiones es el caso de los «préstamos zombis» de los bancos japoneses para salvar a las empresas plagadas de deudas incobrables, lo que condujo a la mala asignación de capital y la desaceleración del crecimiento económico durante la década de 1990 (Caballero, Hoshi y Kashyap, 2008).…”
Section: Fuente De Datos Y Variablesunclassified